2011
DOI: 10.1007/s00128-011-0236-9
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Multiple Esterases as Biomarkers of Organophosphate Exposure and Effect in Two Earthworm Species

Abstract: Two different earthworm species, Eisenia fetida and Lumbricus terrestris, were exposed to 5 μg/cm2 of malathion to evaluate their usefulness as sentinels of organophosphate exposure and to assess three different esterases, as biomarkers of malathion exposure and effect. Tissue xenobiotic burdens and esterase activity were determined for each species and each esterase in order to assess variability. E. fetida exhibited 4-fold less variability in tissue burdens than did L. terrestris and had less variable basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This result was expected since diazinon is an organophosphate and it is known that organophosphorus compounds cause the inhibition of both AChE and CES activity (reviewed in [53]). Although most commonly AChE is screened as a biomarker to organophosphate exposure (e.g., [54,55]), several studies have shown that CES can be a more sensitive indicator to organophosphates than AChE (e.g., [56,57]). In a previous study assessing diazinon effects on zebrafish, a higher sensitivity of CES was demonstrated and it was concluded that later stages of zebrafish have higher sensitivity to diazinon exposure [14].…”
Section: Discussionmentioning
confidence: 99%
“…This result was expected since diazinon is an organophosphate and it is known that organophosphorus compounds cause the inhibition of both AChE and CES activity (reviewed in [53]). Although most commonly AChE is screened as a biomarker to organophosphate exposure (e.g., [54,55]), several studies have shown that CES can be a more sensitive indicator to organophosphates than AChE (e.g., [56,57]). In a previous study assessing diazinon effects on zebrafish, a higher sensitivity of CES was demonstrated and it was concluded that later stages of zebrafish have higher sensitivity to diazinon exposure [14].…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers found in aquatic and terrestrial organisms following exposure to pesticides have been intensively studied in order to predict the presence of pesticides in the environment (Henson-Ramsey et al, 2011;Jamec et al, 2010). Recently, many studies have reported the use of terrestrial organisms for developing biomarkers in response to residual pesticides (Henson-Ramsey et al, 2011;Radwan and Mohamed, 2013;Stepić et al, 2013), and among these, earthworms were widely used to understand the impacts of pesticides in the environment. In two earthworm species, Eisenia fetida and Lumbricus terrestris, multiple esterases, including acetylcholinesterase (AChE), butyrylcholinesterase, and carboxylesterase (CE), have been assessed as biomarkers for malathion exposure (HensonRamsey et al, 2011).…”
Section: Introductionmentioning
confidence: 99%